HUBUNGAN USIA DAN PARITAS TERHADAP KEJADIAN BABY BLUES SYNDROME PADA IBU POSTPARTUM DI KECAMATAN SAMBELIA, LOMBOK TIMUR - Elin Nur Almida; Yolly Dahlia; Ronanarasafa; Adib Ahmad Shammakh (Yayasan Nusantara Hasana Berdikari, 2023)
Baby blues syndrome is a symptom of changes regarding significant mood changes experienced by postpartum mothers, where baby blues syndrome is the mildest form of depression, usually occurring between days 2 to 2 weeks postpartum. Psychological changes experienced by postpartum mothers occur due to hormonal changes that occur after giving birth, high stress levels, age during pregnancy, lack of social support, parity and partner dissatisfaction are common factors that can cause baby blues syndrome. The type of research used in this research is quantitative analytic observational with a cross-sectional study design. The sampling technique was determined by the total sampling method. And the samples in this study were all postpartum mothers on the 7th-14th day of childbirth in the Sambelia sub-district, East Lombok. From the results of the bivariate test, statistically, there was no significant correlation between postpartum maternal age and the incidence of baby blues syndrome with a p-value (p=0.138 > 0.05) and a significant relationship was found between parity and the incidence of baby blues syndrome with a value p<0.05 (p=0.011) which means there is a significant correlation between parity and the incidence of baby blues syndrome. The conclusion of this study, there is no significant correlation between postpartum maternal age and the incidence of baby blues syndrome in Sambelia District, East Lombok and there is a significant correlation between parity and the incidence of baby blues syndrome in Sambelia District, East Lombok.